Criticality of infrastructures for organisations. (2016) - Giovinazzi, Sonia; Brown, Charlotte; Seville, Erica; Stevenson, Joanne R.; Hatton, Tracy; Vargo, John J.
Critical infrastructure systems provide for the circulation of people, goods, services and information upon which health, safety, comfort and economic activity of a society depend. In this study, we analyse data from 541 organisations affected by the 2010-2011 Canterbury, New Zealand, earthquake to understand how disruption of critical infrastructure services translates into disruption for businesses and other organisations affected by the loss of infrastructure services. The paper proposes metrics for assessing the relevance and criticality of infrastructures for organisations. In this context, relevance refers to organisations' perceived reliance on infrastructure services and criticality refers to the impact that infrastructure service outage might have on organisations, as a function of the infrastructure relevance for the same organisations and of the duration of infrastructure service outage. The metrics and procedures proposed in this paper provide a much-needed contribution towards enhancing understanding of the private sector's vulnerability to infrastructure disruption. The study findings can be used to qualitatively assess the vulnerability of industry sectors to infrastructure disruption, and can support the estimation of potential impacts induced by infrastructure service outages, at organisation and industry sector level. This can inform and foster public and private sector investments to enhance infrastructure resilience.